2019
DOI: 10.14569/ijacsa.2019.0100833
|View full text |Cite
|
Sign up to set email alerts
|

Robust Video Content Authentication using Video Binary Pattern and Extreme Learning Machine

Abstract: Recently, due to easy accessibility of smartphones, digital cameras and other video recording devices, a radical enhancement has been experienced in the field of digital video technology. Digital videos have become very vital in court of law and media (print, electronic and social). On the other hand, a widely-spread availability of Video Editing Tools (VETs) have made video tampering very easy. Detection of this tampering is very important, because it may affect the understanding and interpretation of video c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Ren et al [10] presented a technique that identifies duplicate regions using the improved Levenshtein distance, but this experiment cannot be applied to identifying duplicate regions using dynamic backgrounds. To extract noise features using temporal correlation, Sadddique et al [11] suggested a technique that merged Int J Elec & Comp Eng ISSN: 2088-8708  the video binary pattern (VBP) and extreme learning machine (ELM) with the radial basis function (RBF), offering better accuracy and low computation costs. The limitation of this method is that video sequences of extremely short lengths cannot be dealt with effectively.…”
Section: Spatial Domain Forgery Detectionmentioning
confidence: 99%
“…Ren et al [10] presented a technique that identifies duplicate regions using the improved Levenshtein distance, but this experiment cannot be applied to identifying duplicate regions using dynamic backgrounds. To extract noise features using temporal correlation, Sadddique et al [11] suggested a technique that merged Int J Elec & Comp Eng ISSN: 2088-8708  the video binary pattern (VBP) and extreme learning machine (ELM) with the radial basis function (RBF), offering better accuracy and low computation costs. The limitation of this method is that video sequences of extremely short lengths cannot be dealt with effectively.…”
Section: Spatial Domain Forgery Detectionmentioning
confidence: 99%